PROPERTIES OF NEW ENVIRONMENTALLY FRIENDLY BIODEGRADABLE INSULATING FLUIDS FOR POWER TRANSFORMERS - Rozga, Pawel (European Scientific Journal, ESJ, 2013)
The problem of using the new environmentally friendly insulating liquids like synthetic and natural esters for power transformers was presented in this article. The positive and negative properties of the esters were described on the basis of a comparison with the most popular insulating liquid like mineral oil. The results of the own experiences and experimental studies were taken into account as well as the results of works presented in the world literature. Conclusions from the analysis indicate that the wide knowledge about ester properties is necessary to correct design process and to proper exploitation of the power transformers filled in esters.